Post‐marketing surveillance of quetiapine fumarate extended‐release tablets in patients with bipolar depression - Taro Kishi; Nakao Iwata; Hiroyuki Irie; Masaru Aikawa (Wiley, 2024)
Abstract Aim This study aimed to verify the real‐world efficacy and safety of quetiapine fumarate extended‐release tablets (Bipresso® 50 mg and 150 mg; marketing authorization holder is KYOWA Pharmaceutical Industry Co., Ltd., Osaka, Japan) in patients with bipolar depression. Methods We performed a post‐marketing surveillance with an observation period of 12 weeks. Results In the safety analysis group (n = 345), adverse drug reactions (ADRs) occurred in 111 patients (32.17%). The most common ADRs (>1%) were somnolence in 55 patients (15.94%), akathisia in 11 (3.19%), dizziness in 10 (2.90%), weight increase in 6 (1.74%), thirst in 5 (1.45%), and hypersomnia, constipation, and nausea in 4 patients each (1.16%). The only severe ADR was one patient of suicidal ideation, and "longer time since the onset of the first episode" (p = 0.011) and "presence of complications" (p < 0.001) were identified as significant risk factors for the occurrence of ADRs. In the efficacy analysis group (n = 265), the average changes from baseline in the total Montgomery-Åsberg Depression Rating Scale (MADRS) score were −7.3 ± 8.8, −12.2 ± 10.7, −16.8 ± 12.7, and −13.2 ± 12.7 points after 4, 8, and 12 weeks, and at the last evaluation, respectively. The mean MADRS total score decrease had no significant association with maximum daily dose, diagnosis, and presence or absence of prior or concomitant treatment for bipolar disorder with mood stabilizers/antipsychotics/antidepressants. Conclusion The efficacy of quetiapine fumarate extended‐release tablets was confirmed in clinical practice, and no new safety concerns or risks were identified.